In Vitro Activity of Ethanol Extract of Rimbang Fruit (Solanum ferox) as an Active Ingredient in Sunscreen Preparations - Kalalinggi, Septaria Yolan; Rasidah; Yuliana (Indonesian Journal of Chemical Analysis (IJCA), 2024)
Solanum ferox is a typical Central Kalimantan plant widely used by Dayak’s community as a vegetable. The study aims to determine the ethanol extract of sour eggplant activities by measuring its SPF in vitro and identifying secondary metabolite contents. The sour eggplant is extracted by maceration using 96% ethanol solvent and then bound with an evaporator. The secondary metabolite groups of ethanol extract were identified using phytochemical screening. The identification results indicate the presence of flavonoid, terpenoid, steroid, and phenolic compounds. Then, the ethanol extract was fractionated with a water solvent, and its functional cluster was identified using the IR spectrum. IR spectral identification results indicate the presence of OH, C-O, C=C olefin, C -O ether, and aliphatic CH functional groups. (CH2 and CH3) SPF values were determined by measuring the absorption of ethanol and water extracts in vitro using UV-Vis spectrophotometry at UV-B wavelengths of 290-320 nm. In vitro testing has been conducted as a preliminary test in developing a sunscreen product (active substance). The SPF values of ethanol extract and water from weighted fruit extract in sequence are 40 and 23 at a 10% concentration with ultra-category.